STRATEGI PENGEMBANGAN WISATA PANTAI KARTINI DI KABUPATEN JEPARA - Kurniyati, Zeny; Astuti, Puji; Widayati, Wiwik (Journal of Politic and Government Studies, 2013)
abstractThis study aims to determine the strategy - what strategies are used byJepara regency government as a business and tourism development Kartini Beachbarriers - barriers experienced by any government in the development of businessKartini Beach attractions. Technical analysis of the data used is a qualitative descriptionas well as a SWOT analysis. The results showed that the strategy used bygovernment is (1) a strategy for regional development, (2) development strategyobject and appeal, (3) development of promotional strategies, and (4) strategiesdevelopment of facilities and infrastructure. And barriers experienced consists of conditionsphysical, developmental conditions and lack of funding.Keywords: Tourism, Strategy Development, Kartini Beach